1990
DOI: 10.1111/j.1469-8749.1990.tb16972.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Impairments of Brain and Auditory Functions of Children Recovered From Purulent Meningitis

Abstract: SUMMARY Sixty children who had recovered from purulent meningitis one to six years earlier were investigated for long‐term impairment of brain and auditory function, using brainstem auditory evoked potentials(BAEP) and developmental screening tests. Neurological and/or audiological BAEP abnormalities were found in 23 per cent of the children: 15 per cent had mild brainstem impairment and 12 per cent had hearing dysfunction. Developmental screening tests were administered to 46 children, of whom 61 per cent had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In a review of 79 children with bacterial meningitis, however, infection with S. pneumoniae was found to be a statistically significant predictor of subsequent sensorineural HL (Wellman, Sommer, & McKenna, 2003). This mechanism is presumed to be due to bacterial spread from the subarachnoid space through the cochlear aqueduct to the labyrinth, resulting in toxic labyrinthitis, ischemia, and/or direct nerve damage (Brookhouser, Auslander, & Meskan, 1988; Jiang, Liu, Wu, Zheng, & Liu, 1990). The optimal treatment of bacterial meningitis is in evolution, but a recent systematic review found that corticosteroid therapy in addition to antibiotics was associated with a statistically significant decrease in neurologic sequelae, including HL.…”
Section: Causes Of Unilateral Hearing Lossmentioning
confidence: 99%
“…In a review of 79 children with bacterial meningitis, however, infection with S. pneumoniae was found to be a statistically significant predictor of subsequent sensorineural HL (Wellman, Sommer, & McKenna, 2003). This mechanism is presumed to be due to bacterial spread from the subarachnoid space through the cochlear aqueduct to the labyrinth, resulting in toxic labyrinthitis, ischemia, and/or direct nerve damage (Brookhouser, Auslander, & Meskan, 1988; Jiang, Liu, Wu, Zheng, & Liu, 1990). The optimal treatment of bacterial meningitis is in evolution, but a recent systematic review found that corticosteroid therapy in addition to antibiotics was associated with a statistically significant decrease in neurologic sequelae, including HL.…”
Section: Causes Of Unilateral Hearing Lossmentioning
confidence: 99%
“…1 Bacterial meningitis in newborns infants remains as a serious disease with significant longterm neurological morbidity. [2][3][4][5] Prediction of outcome is important in decision-making to provide information to parents, and for identification of subjects requiring close intervention and early follow-up. Clinical evaluation includes neurological examination, cerebrospinal fluid (CSF) culture, neuroimaging studies and neurophysiological studies, such as the electroencephalogram (EEG) and evoked potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dos avanços diagnósticos e terapêuticos ocorridos nos últimos anos, a meningite piogênica continua sendo um problema de saúde pública, sobretudo nos países em desenvolvimento (1)(2) . Embora tenha distribuição universal, sua frequência é variável.…”
Section: Introductionunclassified